If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(r + 3) = 14 Reorder the terms: 2(3 + r) = 14 (3 * 2 + r * 2) = 14 (6 + 2r) = 14 Solving 6 + 2r = 14 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2r = 14 + -6 Combine like terms: 6 + -6 = 0 0 + 2r = 14 + -6 2r = 14 + -6 Combine like terms: 14 + -6 = 8 2r = 8 Divide each side by '2'. r = 4 Simplifying r = 4
| w-16.7=8.2 | | -16.97=-8.69+-2b | | 152-5x=22x+23 | | 207=10w | | 6-7x=18-14x | | 568-264=x | | 0.2+3=0.1y+0.7 | | 217=10w+10 | | -69-10x=8x+21 | | 284-568=x | | 3(k-1)= | | (x+5)9= | | 7.57-2y=2.37 | | 3p-1.8=11.34 | | 4.75h+2.00c=568 | | 4M+7=7M+22 | | 19v-13=386 | | 114.6=6w | | 2(8n+7)=-50+2(-5n+6) | | 4.75h+2.00(284+-2.375h)=160*3.55 | | 5(-15k+75)=8+11k | | 4.75h+2.00c=160*3.55 | | 128.6=6w+14 | | 69x+33=13-4 | | 4.75x+2.0(160-x)=3.55 | | 699=5p+104 | | 9+2t-6=9t+11-6t | | -6=x-34 | | 5(x+3)=-15 | | 2(5x-6)=(3x-2)+4 | | -4.9(x-1)-6.8(x-0.8)=-38.8 | | 3y-30=6y+30 |